Exposure to glyphosate and risk of non-Hodgkin lymphoma: an updated meta-analysis: Exposure to glyphosate and risk of non-Hodgkin lymphoma - Boffetta, Paolo; Ciocan, Catalina; Zunarelli, Carlotta; Pira, Enrico (La Medicina del Lavoro, 2021)
Objective: We updated a recent systematic review and meta-analysis of epidemiologic studies to help clarifying the association between exposure to glyphosate and risk of non-Hodgkin lymphoma (NHL). Methods: We conducted an updated search of the literature, and identified a total of 15 relevant publications, from which we extracted results from six non-overlapping studies. We performed random-effects meta-analyses for ever-exposure to glyphosate, dose-response, and risk of specific NHL subtypes Results: The meta-RR for ever-exposure to glyphosate was 1.05 (95% confidence interval [CI] 0.90-1.24; I2 = 0%). The meta-RR for the highest category of exposure was 1.15 (95% CI 0.72-1.83; 3 studies). The meta-RR for diffuse large B-cell lymphoma (DLBCL) was 1.29 (95% CI 1.02-1.63; 4 studies), that for follicular lymphoma was 0.84 (95% CI 0.61-1.17), and that for chronic lymphocytic leukemia/small lymphocytic lymphoma was 1.33 (95% CI 0.65-2.70). There was indication of publication bias. Conclusions: This updated meta-analysis reinforces our previous conclusion of a lack of an association between exposure to glyphosate and risk of NHL overall, although an association with DLBCL cannot be ruled out.